Recycling of Tennis Balls in the European Union on the example of the Czech Republic - Cintl, Matěj (2022)
This bachelor thesis deals with the issue of recycling tennis balls in the European Union on the example of the Czech Republic. The main goal of this work is to find a sustainable solution for recycling of tennis balls, which could also serve as an inspiration for other sports. The case study consists of an interview with the CEO of the only tennis ball recycling company in the Czech Republic, called Dropp, which has the ambition to be a solution for the whole of Europe. The secondary goal of this bachelor thesis is to provide ideas and strategies for possible solutions to the problem of waste in sports, especially in tennis. Among other things, this work also contains a list of already functioning recycling projects around the world, compares how similar they work and how successful they are.